Dynamic properties of hybrid composite structures based multiwalled carbon nanotubes. (18th August 2017) - Benyahia, H.; Tarfaoui, M.; Datsyuk, V.; El Moumen, A.; Trotsenko, S.; Reich, S.
Abstract: The present paper investigates an experimental approach concerning the determination of dynamic behavior and damage kinetics of composite materials based on multiwalled carbon nanotubes (MWCNTs), embedded in electrospun reactive nanofibers in the Taylor impact test. Different impact energies have been considered namely; 21J and 39J to investigate the composite response. Projectiles are manufactured from a commercial steel 2071 with a nominal diameter of 50 mm and 1600 g of weight. The projectile was fired against a composite specimen initially hooked on a cell effort by a compressed gas gun within the velocity of 5 m/s and 7 m/s. Three types of specimens are considered: (1) MAT1 (carbon fiber reinforced epoxy polymer composite), MAT2 (consists of MAT1 and electrospun Polybenzmideazole-Bismaleimide (PBI-BMI) nanofibermats between carbon fiber layers) and MAT3 (consists of MAT2, where PBI-BMI nanofibermats are reinforced with multiwalled carbon nanotubes (MWCNTs)). The effect of the MWCNTs on the dynamic properties of the composite structures was studied. Microscope observations reveal damage progressive, buckling and crush-front propagation during tests. Application of the PBI-BMI reactive nanofibermats reinforced with MWCNTs leads to damage prevention, reducing damage area in composite samples.